Hands-On Deep Learning Architectures with Python : Create Deep Neural Networks to Solve Computational Problems Using TensorFlow and Keras. - Liu, Yuxi (Hayden) (Packt Publishing, Limited, 2019)
This book explains the essential learning algorithms used for deep and shallow architectures. Packed with practical implementations to help you understand the concepts and ideas required to build efficient artificial intelligence systems, this book will help you construct deep models using popular frameworks and datasets.